Breast Implant-associated Anaplastic Large Cell Lymphoma after Breast Reconstruction for Breast Cancer - Felipe Mesa, MD, PhD; Julián Bernal Arrubla, MD; Luis Javier Gallón, MD; Gustavo Matute Turizo, MD; Diana Marcela Caicedo Ruiz, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
A patient initially operated on for aesthetic breast augmentation had a round-textured silicone gel prosthesis, Poly Implants Prothèse, placed in a subglandular plane. The patient developed a bilateral capsular contracture, and 4 years later, underwent a complete bilateral capsulectomy with an exchange of Mentor 215 cm3 textured cohesive silicone-gel ultra-high profile breast implants in the same subglandular plane. One year later, the patient developed cancer in the right breast, so it was decided to perform a bilateral mastectomy and reconstruction with 265 cm3 (left) and 310 cm3 (right) Natrelle (Allergan) round-textured silicone-gel implants in a submuscular plane. Seven years after the last surgery, the patient developed a seroma in the left breast (breast opposite to the one that developed the cancer), and seroma studies reported a CD30-positive anaplastic large cell lymphoma associated with the breast prosthesis. Therefore, bilateral capsulectomy and explantation of both implants with breast reconstruction with autologous tissue were performed.